2015
DOI: 10.1111/phn.12179
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Unintentional Injury among University Students in 26 Countries

Abstract: Several risk factors were identified which will increase the understanding of public health nurses of injuries in university communities to design programs for injury prevention programs specifically targeting university students, staff, and university health center professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Almost half of participants (47.9%) experienced an unintentional injury during the past year, which is much higher than reported by international studies conducted with a student population. 7 8 Previous studies from 26 countries displayed a substantial variation in reported unintentional injury prevalence among college students from 14% to 39.7% 7. Several domestic regional studies showed that the annual prevalence of unintentional injury among Chinese college students was 18.7% in Wenzhou city,8 48.7% in Dali city,18 64.9% in Wuhu city19 and 51.0% (only for sport injury) in Guangzhou city 20.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Almost half of participants (47.9%) experienced an unintentional injury during the past year, which is much higher than reported by international studies conducted with a student population. 7 8 Previous studies from 26 countries displayed a substantial variation in reported unintentional injury prevalence among college students from 14% to 39.7% 7. Several domestic regional studies showed that the annual prevalence of unintentional injury among Chinese college students was 18.7% in Wenzhou city,8 48.7% in Dali city,18 64.9% in Wuhu city19 and 51.0% (only for sport injury) in Guangzhou city 20.…”
Section: Discussionmentioning
confidence: 98%
“…It is the leading cause of death in nearly every region of the world, and the second leading cause of potentially productive life years lost due to disability worldwide among young people (10–24 years old) 7. In comparison with other age groups, injuries among youth and especially among undergraduates caused more direct and indirect economic and social loss to families and countries 8.…”
Section: Introductionmentioning
confidence: 99%
“…A poor psychopathology status was associated with an increased risk of unintentional injuries among adolescents, with baseline psychological sub-healthy status being a predictive factor for higher risk of unintentional injuries [ 40 ]. Lack of personal control has been associated with injury incidence in university students in 26 countries [ 41 ]. The results of these studies are consistent with our findings and support our initial hypothesis that emotional and behavioral symptoms were related to injuries.…”
Section: Discussionmentioning
confidence: 99%
“…University students may be particularly vulnerable to injury, PTSD, and depressive symptoms. For example, in a study among university students in 26 countries the prevalence of past 12-month injury was 25.2% [3]. In a review of 37 studies among university students in 20 countries, the overall prevalence of depressive symptoms was 24.4% [4], and in a study among university students from 22 countries, the prevalence of PTSD symptoms was 20.9% [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to those in high-income countries, there may be a greater lack of availability of both care for injuries and mental health in low-resourced countries [13]. Given the high prevalence of physical injury among university students in low resourced settings [3], the analysis of the potential impact of physical injury on mental health outcomes would be of outmost relevance. Therefore, this study is filling gaps in the evidence on the relationship between physical injury, PTSD, and depressive symptoms in a population survey among university students.…”
Section: Introductionmentioning
confidence: 99%